SAT0102 Influence of Vaccination Program To Prevent Acute Respiratory Infection in Rheumatoid Arthritis. (15th July 2016) - Rodriguez-Cundin, P.; Calvo-Río, V.; Blanco, R.; Dominguez-Casas, L.C.; Vegas-Revenga, N.; Fernández Díaz, C.; Portillo, V.; Antolin, F.M.; Rebollo-Rodrigo, M.H.; Gonzalez-Gay, M.A.
Abstract : Background: Patients with autoimmune rheumatic diseases such as rheumatoid arthritis (RA) are at increased risk for infections, especially respiratory type. Immunization is a recommended measure to reduce these complications. Objectives: Assess the incidence of acute respiratory infections (ARI), defined as one that causes hospitalization, before and after inclusion in a systematic vaccination program. Methods: Prospective study in a cohort of 294 patients diagnosed with RA, were included in the vaccination program. This program includes: seasonal flu vaccine (october to april), pneumococcal (combined regimen 13-valent and 23-valent) and Haemophilus influenzae B. Only 7 patients (2.94%) refused vaccination. The follow-up time was from October 1st, 2011 (starting date) to June 30th, 2015. Information on ARI episodes before and after immunization was collected from the Hospital Information System, reviewing hospital records. Results: 287 RA patients (225 women/62 men) were vaccinated, with an average age of 58.1 ± 12.7 years. RA was characterized at the time of vaccination by the time of evolution of RA 93 ± 95.9 months; 154 (53.65%) positive RF, 97 (33.8%) erosive and 40 (13.9%) with extra-articular manifestations (7 with pulmonary fibrosis). Only 42 (14.6%) were not taking any immunosuppressive or immunomodulatory therapy at the time of immunization. 147 patients were treated with Disease Modifying Antirheumatic Drugs (DMARD's), mainly methotrexate, and 98 patients (34.1%) were with a TNFa inhibitor. Regarding the ARI, before inclusion in the vaccination program, 20 (7%) patients in the cohort studied had been admitted into the hospital for this reason. During follow-up, and subsequent immunization, only 6 of the 287 patients (2.1%) had ARI (Table 1 ). One of them had an ARI prior to vaccination program. This reduction from 7% to 2.1% achieved statistically significant difference (p=0.0017). Conclusions: Incorporating a program of systematic vaccination in RA patients appears to be an effective prophylactic measure to prevent the ARI. Disclosure of Interest: None declared